Understanding the epidemiology of avoidable significant harm in primary care: protocol for a retrospective cross-sectional study - Bell, Brian; Campbell, Stephen; Carson-Stevens, Andrew; Prosser Evans, Huw; Cooper, Alison; Brindley, Christina; Rodgers, Sarah; Johnson, Christine; Edwards, Adrian; Armstrong, Sarah; Mehta, Rajnikant; Chuter, Antony; et al. (BMJ Publishing Group Ltd, 2017)
Introduction: Most patient safety research has focused on specialist-care settings where there is an appreciation of the frequency and causes of medical errors, and the resulting burden of adverse events. There have, however, been few large-scale robust studies that have investigated the extent and severity of avoidable harm in primary care. To address this, we will conduct a 12-month retrospective cross-sectional study involving case note review of primary care patients.